The effect of wear on nucleation of cracks at the edge of an almost complete contact - Hills, D; Paynter, R; Nowell, D (2010)
A contact with a flat region and a rounded corner will have adhered and slipping regions and a locally non-singular contact traction distribution. When wear occurs in the slipping region, the geometry and thus the pressure distributions change. An analytical asymptotic analysis of the edge of this "almost complete" contact shows that wear will leave a complete contact with the same extent as the original adhered region and a singular traction distribution. © 2009 Elsevier B.V. All rights reserved.